Manajemen Penanaman Sayuran Organik dan Pemanfaatan Limbah Pertanian sebagai Pupuk Organik di Desa Lambunot Paya, Kuta Baru-Aceh Besar - Mardhiah, Hayati; Nurhayati, Nurhayati; Marliah, Ainun; Nura, Nura; Hayati, Erita (Universitas Syiah Kuala, 2023)
Modern agriculture is characterized by the utilization of inputs like inorganic fertilizers, mainly due to the cultivation of superior varieties that respond well to fertilization (especially artificial fertilizers) and are resistant to pesticides. This practice is adopted to address the growing urgency of food demands. However, the utilization of these materials has led to critical issues concerning land degradation due to negative impacts from inorganic fertilizers and pesticides. One approach to encourage sustainable farming practices is through community service programs that offer training and outreach to raise awareness about the significance of using organic fertilizers and pesticides in plant cultivation. The training conducted in Lambunot Paya Village focuses on promoting organic farming by teaching farmers to comprehend and embrace organic techniques. It includes instruction on creating compost and bokashi, producing organic pesticides/biopesticides, and adopting organic vegetable cultivation methods employing organic fertilizers and pesticides. The benefits of this initiative are evident in increased crop yields, environmental and consumer health preservation, and efficient use of agricultural waste. Moreover, it aligns with the government's objectives of enhancing agricultural yields while safeguarding the environment, human health, and biodiversity, along with curbing pest and disease outbreaks. Ultimately, this contributes to maintaining high agricultural productivity and ensuring long-term soil fertility